2022
DOI: 10.1097/nna.0000000000001113
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Partnership Unit

Abstract: Recruitment and retention of BSN-prepared nurses are a primary goal of many hospitals as they attempt to meet the challenges of high patient acuities and increased turnover among bedside nurses. In this article, the authors describe the Academic Partnership Unit, an evidence-based clinical education program designed to train, recruit, and retain BSN-prepared nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The positive impact of the onboarding program [ 34 , 37 , 42 , 57 , 62 , 63 , 67 , 77 ] and mentorship [ 51 , 73 , 80 , 90 ] is in line with earlier published systematic reviews [ 91 , 92 ]. Kakyo et al [ 93 ] explored the benefits of the informal mentoring program for nurses and confirmed that built on the reciprocal relationship between mentee and mentor; there is a substantial benefit of the mentoring program.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The positive impact of the onboarding program [ 34 , 37 , 42 , 57 , 62 , 63 , 67 , 77 ] and mentorship [ 51 , 73 , 80 , 90 ] is in line with earlier published systematic reviews [ 91 , 92 ]. Kakyo et al [ 93 ] explored the benefits of the informal mentoring program for nurses and confirmed that built on the reciprocal relationship between mentee and mentor; there is a substantial benefit of the mentoring program.…”
Section: Discussionsupporting
confidence: 79%
“…Four of the included studies mainly focused on the onboarding program on the transition from nursing school towards the first job as a nurse and started at the last stage of nursing school [ 34 , 57 , 62 , 77 ]. First, Tseng et al [ 77 ] studied an extensive externship program (EP), the Corporate-Academic Cooperation Program (CACP), to bridge the gap from nursing school to a clinical setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations